American Civil Liberties Union of Northern California Honors Howard Watkins with Lola Hanzel Courageous Advocacy Award - Watkins, Howard::::::::: (1987)
Howard Watkins thanking the staff and many American Civil Liberties Union supporters for their work Luncheon at Sheraton Palace Hotel in San Francisco